HIV Variability in the Liver and Evidence of Possible Compartmentalization - Blackard, Jason T. (Mary Ann Liebert, Inc., 2011)
There is growing evidence to suggest that HIV may interact with several hepatic cell types; however, evaluation of HIV variability in liver tissue has not been addressed to date. Among 16 HIV-positive individuals examined, nine (56%) had detectable HIV RNA in the liver. The mean CD4 cell count for these nine individuals was 337 cells/mm(3) (range: 0–601), while their mean plasma HIV RNA level was 106,974 copies/ml (range: 1200–320,740). Among individuals in this study with detectable HIV in both the plasma and the liver, the consensus gag nucleotide sequences for each tissue type were different for seven of seven (100%) individuals, while amino acid sequences were distinct for five of seven (71%). Consensus envelope (env) nucleotide and amino acid sequences were also distinct in the plasma and liver tissue for six of six (100%) individuals. Statistical evidence of compartmentalization between HIV in the plasma and in the liver was demonstrated, and multiple liver-specific amino acids were identified that may distinguish HIV variants replicating within the liver. These preliminary data demonstrate that HIV is frequently detectable in the liver of HIV-positive persons at various levels of immunosuppression. Possible compartmentalization may reflect tissue-specific selection pressures that drive viral adaptation to the liver microenvironment and may facilitate interactions with other hepatotropic viruses.